(untitled) (Revista Latino-Americana de Enfermagem, 2012)
This study aimed to describe the development and validation of three multidimensional scales in which the same 30 items, distributed among five dimensions, measure parents' self-perceived confidence, difficulties and knowledge needs in the exercise of positive parenting during the first three years of the child's life. The content of the scales resulted from the literature and exploratory studies and was validated by experts. The analysis of its reliability and validity, using Pearson's correlations and Cronbach's alpha, was based on data from a questionnaire administered to a non-probabilistic sample of 1011 parents. In the dimensions and items, α-values ranged between 0.769 and 0.890 and r-coefficients were >0.37;p